Corrected QTc interval combined with troponin value and mortality in acute ischemic stroke - Ahn, Sung-Ho; Lee, Ji-Sung; Yun, Mi-sook; Han, Jung-Hee; Kim, Soo-Young; Lee, Sang-Hyun; Park, Min-Gyu; Park, Kyung-Pil; Kang, Dong-Wha; Kim, Jong S.; Kwon, Sun U. (Frontiers in Cardiovascular Medicine, 2023)
Background and Purpose Cardiac biomarkers including, elevated troponin (ET) and prolonged heart rate-corrected QT (PQTc) interval on electrocardiography are known to frequent and have a prognostic significance in patients with acute ischemic stroke (AIS). However, it is still challenging to practically apply the results for appropriate risk stratification. This study evaluate whether combining ET and PQTc interval can better assess the long-term prognosis in AIS patients. Methods In this prospectively registered observational study between May 2007 and December 2011, ET was defined as serum troponin-I ≥ 0.04 ng/ml and PQTc interval was defined as the highest tertile of sex-specific QTc interval (men ≥ 469 ms or women ≥ 487 ms). Results Among the 1,668 patients [1018 (61.0%) men; mean age 66.0 ± 12.4 years], patients were stratified into four groups according to the combination of ET and PQTc intervals. During a median follow-up of 33 months, ET (hazard ratio [HR]: 4.38, 95% confidence interval [CI]: 2.94–6.53) or PQTc interval (HR: 1.53, 95% CI: 1.16–2.01) alone or both (HR: 1.77, 95% CI: 1.16–2.71) was associated with increased all-cause mortality. Furthermore, ET, PQTc interval alone or both was associated with vascular death, whereas only ET alone was associated with non-vascular death. Comorbidity burden, especially atrial fibrillation and congestive heart failure, and stroke severity gradually increased both with troponin value and QTc-interval. Conclusions In patients with AIS, combining ET and PQTc interval on ECG enhances risk stratification for long-term mortality while facilitating the discerning ability for the burden of comorbidities and stroke severity.